The Effectiveness of the Joint Commission International Accreditation in Improving Quality at King Fahd University Hospital, Saudi Arabia: A Mixed Methods Approach - Al Shawan D (Dove Medical Press, 2021)
Deema Al Shawan College of Public Health, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Deema Al ShawanCollege of Public Health, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaEmail dshawan@iau.edu.saIntroduction: Saudi Arabia has one of the highest numbers of health organizations accredited by the Joint Commission International. This study aimed to measure this process’s effectiveness in improving quality at King Fahd Hospital of the University in Khobar, Saudi Arabia. Additionally, the study investigated health providers’ perceptions of this process.Materials and Methods: This research utilized a convergent parallel mixed method. For the quantitative analysis, an interrupted time series was conducted to assess the changes in a total of 12 quality outcomes pre- and post-accreditation. Thematic analysis was utilized to collect and analyze qualitative data from hospital employees and health providers.Results: The quantitative results indicated that pursuing accreditation positively impacted nine out of 12 outcomes. The improved outcomes included: the average length of stay, the percentage of hand hygiene compliance, the rate of nosocomial infections, the percentage of radiology reporting outliers, the rate of pressure ulcers, the percentage of the correct identification of patients, the percentage of critical lab reporting, and the bed occupancy rate. The outcomes that did not improve were the rate of patients leaving the ER without being seen, the percentage of OR cancelations, and the rate of patient falls. The qualitative analysis suggested that the accreditation process was perceived positively by participants. Nevertheless, participants also highlighted some of the drawbacks of this process, including: the potential bias in observation-based key performance indicators, the focus on improving process without enhancing the hospital structure, and the increased workload.Conclusion: International accreditation had a positive impact on quality and was received positively by providers. However, several issues need to be addressed by hospital administrators in future accreditation cycles. According to participants, the most notable issue during the first two accreditation cycles was the increased workload and paperwork, which can potentially distract from patient care.Keywords: Joint Commission International, interrupted time series analysis, JCI, mixed methods, Saudi Arabia, JCIA